Consequences of electroshock‐induced narcosis in fish muscle: from mitochondria to swim performance. Issue 6 (23rd April 2018) - Teulier, L.; Guillard, L.; Leon, C.; Romestaing, C.; Voituron, Y.
Abstract : Adult zebrafish Danio rerio were exposed to an electric shock of 3 V and 1A for 5 s delivered by field backpack electrofishing gear, to induce a taxis followed by a narcosis. The effect of such electric shock was investigated on both the individual performances (swimming capacities and costs of transport) and at cellular and mitochondrial levels (oxygen consumption and oxidative balance). The observed survival rate was very high (96·8%) independent of swimming speed (up to 10 body length s −1 ). The results showed no effect of the treatment on the metabolism and cost of transport of the fish. Nor did the electroshock trigger any changes on muscular oxidative balance and bioenergetics even if red muscle fibres were more oxidative than white muscle. Phosphorylating respiration rates rose between (mean 1 s.e. ) 11·16 ± 1·36 pmol O2 s −1  mg −1 and 15·63 ± 1·60 pmol O2 s −1  mg −1 for red muscle fibres whereas phosphorylating respiration rates only reached 8·73 ± 1·27 pmol O2 s −1  mg −1 in white muscle. Such an absence of detectable physiological consequences after electro‐induced narcosis both at organismal and cellular scales indicate that this capture method has no apparent negative post‐shock performance under the conditions of this study.